2013
DOI: 10.4236/asm.2013.33a001
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Levels and Development of the Penile Spines and Testicular Tissue during the Postnatal Growth in Wistar Rats

Abstract: Aim of Study: Gonadal hormones exert a profound influence on the development, structure and function of the sexual organs. The testosterone is one of the androgens that plays an essential role in the development of sexual organs in male mammals. Therefore, the present study was undertaken to evaluate the testosterone levels and developmental pattern of the penile spines and seminiferous tubules during early postnatal life of Wistar rats. Methods and Materials: At 7, 14, 21, 28, 35, 42, 49, 56, 63 and 70 days a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
1
10
0
1
Order By: Relevance
“…Epidermal or genital spines occur in other mammals such as primates, rodents, carnivores, and insectivores (Aronson and Cooper, 1967;Lidicker and Yang, 1986;Ryan, 1991aRyan, , 1991bStockley, 2002;Kamikawa-Miyado et al, 2005;Silva et al, 2013), where they vary greatly in morphology and size. They are not restricted to mammals, additionally occurring in other groups of animals such as insects, snakes and waterfowl (Waage, 1979;Rönn et al, 2007;Friesen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal or genital spines occur in other mammals such as primates, rodents, carnivores, and insectivores (Aronson and Cooper, 1967;Lidicker and Yang, 1986;Ryan, 1991aRyan, , 1991bStockley, 2002;Kamikawa-Miyado et al, 2005;Silva et al, 2013), where they vary greatly in morphology and size. They are not restricted to mammals, additionally occurring in other groups of animals such as insects, snakes and waterfowl (Waage, 1979;Rönn et al, 2007;Friesen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The neonatal testosterone surge contributes to brain masculinization [2]. In the third pubertal surge, the testosterone level starts to rise in 12-year old in humans [15], and increases until a peak in the early 20s; the equivalent rise starts at 5-6 weeks of age in rats [16,17] and at 4 weeks of age in mice [10,18]. This pubertal testosterone rise contributes to the development of secondary sexual characteristics and reproductive capacity.…”
Section: Blood Testosterone Levels In Lifementioning
confidence: 99%
“…Other studies have shown that sexual motivation in male rats is related to increased serum T levels (Bonilla-Jaime et al, 2006). During puberty, this hormone plays an organizational role that facilitates the morphological and behavioral changes associated with sexual maturation (Hernández-González, 2000;Schulz et al, 2004;Arteaga-Silva et al, 2013;Hernández-González et al, 2015). As mentioned previously, corticosterone exerts a negative effect on T levels (Retana-Márquez et al, 2003), so it is likely that the stress paradigm used herein increased corticosterone levels (Serra et al, 2005;Perelló et al, 2006;Amistislavskaya et al, 2013) during puberty and so exerted a long-term negative effect on T levels that led the stressed rats to manifest lower levels than controls in adulthood.…”
Section: Discussionmentioning
confidence: 96%
“…Animal models have also shown the deleterious effects of stress on sexual behavior (Retana-Márquez, Bonilla-Jaime, Vázquez-Palacios, Martínez-García, & Velázquez-Moctezuma, 2003;Hernández-González, Guevara, Ramírez-Rentería, & Hernández-Arteaga, 2015;Hernández-González et al, 2017), which can vary with stressor type, duration, and the period when it occurs (Lapiz et al, 2003;Vetulani, 2013;Hernández-Arteaga et al, 2016;Hernández-González et al, 2017). Puberty is a critical period for sexual maturation as important hormonal changes occur to allow adequate manifestations of sexual behavior during adulthood (Duffy & Hendricks, 1973;Cooke, Chowanadisai, & Breedlove, 2000;Hernández-González, 2000;Arteaga-Silva et al, 2013). Gonadal hormones like testosterone (T) and its metabolites (Bonilla-Jaime, Vázquez-Palacios, Arteaga-Silva, & Retana-Márquez, 2006) are crucial to sexual behavior.…”
Section: Introductionmentioning
confidence: 99%